Impact of workplace incivility against new nurses on job burn-out: a cross-sectional study in China. Issue 4 (5th April 2018) - Shi, Yu; Guo, Hui; Zhang, Shue; Xie, Fengzhe; Wang, Jinghui; Sun, Zhinan; Dong, Xinpeng; Sun, Tao; Fan, Lihua
Abstract : Abstract: This study had three objectives: (1) to investigate the impact of workplace incivility on job burn-out of new nursing staff, (2) to verify the partial mediating role of anxiety in the relationship between workplace incivility and job burn-out, (3) to examine the resilience moderating the relations between workplace incivility and job burn-out. Design: A cross-sectional online survey was conducted in May 2016 in China. Setting: The survey was conducted in 54 cities across 29 provinces of China. Participants: A total of 903 participants were invited. Ultimately, 696 new nurses (<3 service years) completed valid questionnaires. The effective response rate was 77.1%. Entry criteria: voluntary participation, having less than three service years and being a registered nurse. Exclusion criteria: being an irregular nurse, having more than three service years and refusing to participate in this work. Outcome measures: An anonymous questionnaire was distributed among new nurses. The relationships and mechanism among the variables were explored using descriptive statistical analysis, Pearson's correlation coefficient and multiple linear regression analysis. Results: The findings showed that workplace incivility was positively correlated with anxiety (r=0.371, p<0.01) and job burn-out (r=0.238, p<0.01) of new nurses. The positive relation between anxiety (β = 0.364, p<0.01) and job burn-out (β = 0.240, p<0.01) was also significant. Moreover, anxiety partially mediated (z=7.807, p<0.01) and resilience moderated (β=−0.564, p<0.01) the association between workplace incivility and job burn-out. Conclusion: Experience of workplace incivility by new nurses would likely generate anxiety in the victims. Further, the increased anxiety state could elevate their level of job burn-out. New nurses with high levels of resilience could buffer the negative influence of workplace incivility by using a positive coping style.